The taming of Lola : a shrew story - Weiss, Ellen, 1949- (Abrams Books for Young Readers, 2010)
Lola, a shrew, is famous all over West Meadow for her temper tantrums, but when her cousin Lester comes for a visit and gets special treatment just because he demands it, Lola begins to rethink her behavior.